Characterization of lignin streams during ionic liquid/hydrochloric acid/formaldehyde pretreatment of corn stalk. (July 2021) - Zhang, Kaili; Sun, Qingqin; Wei, Ligang; Sun, Jian; Li, Kunlan; Zhang, Junwang; Zhai, Shangru; An, Qingda
Highlights: FA stabilized lignin was obtained from [C4 C1 im]Cl/HCl/FA pretreatment of biomass. FA stabilization influenced structure feature of lignin fractions. Lignin with high molecular weight and low S/G ratio was recovered. FA stabilization changed the compositions of degraded products from lignin. Abstract: This work investigated the role of formaldehyde (FA) in lignin anti-condensation during corn stalk pretreatment based on 1-butyl-3-methylimidazolium chloride ([C4 C1 im]Cl)/hydrochloric acid (HCl). As a result of the aldolization reactions between FA and lignin, the condensation of lignin fragments was inhibited, and lignin remained in soluble fragmental molecules. Characterizations on the compositional and structural changes of lignin and its degraded products during pretreatment (80 °C–100 °C, 2–5 h) with FA addition in comparison with those in DO/HCl/FA or [C4 C1 im]Cl/HCl were conducted. Results revealed that the structural features of lignin were affected by FA addition and solvent type. In the [C4 C1 im]Cl/HCl/FA system, FA stabilization was unfavorable for the cleavage of β -O-4′ bonds and lignin with low S/G ratio (3.4) and high molecular weight (Mw = 9920 g·mol −1 ) was extracted. The compositions of degraded products were considerably affected by FA addition.